PENINGKATAN PEMAHAMAN KIMIA MELALUI PADUAN PEMBELAJARAN KOOPERATIF DAN PEMECAHAN MASALAH KIMIA DENGAN TEKNIK PATHWAY - Muntari Muntari (Universitas Negeri Malang, 2016)
Abstract: Improving Students' Understanding of Chemistry through the Combination of Learning Together (LT) Model of Cooperative Learning and Pathway Technique. The aim of the study is to know the effect of combination of LT model of cooperative learning and pathway technique of chemistry problem solving to student's conceptual and algorithmic understanding. The study was carried out in State Senior High School 1 Mataram; the subjects consisted of students of two study groups, XI IPA-2 and XI IPA-6 (treated with LT model of cooperative learning), meanwhile XI IPA-3 and XI IPA-5 were treated with direct instruction. Pathway problem solving served as control variable used by two groups of students. The data were analyzed by One-way Analysis of Variance (ANOVA). It was found that the application of combination of LT model of cooperative learning and pathway technique of chemistry problem solving showed was no difference in the student's conceptual understanding compared to direct instruction. However, the application of combination of LT model cooperative learning and pathway technique of chemistry problem solving showed the significant difference in the student's algorithmic understanding compared to direct instruction. The combined LT model of cooperative learning and pathway technique of chemistry problem solving produced a better result than direct instruction in the achievement of student's algorithmic understanding in chemistry. Abstrak: Peningkatan Pemahaman Kimia Melalui Paduan Pembelajaran Kooperatif dan Pemecahan Masalah Kimia dengan Teknik Pathway. Penelitian ini  bertujuan untuk mengetahui pengaruh paduan pembelajaran kooperatif model Learning Together ( LT) dan pemecahan masalah kimia dengan teknik pathway terhadap pemahaman konseptual dan algoritmik kimia siswa. Penelitian dilakukan di SMA Negeri 1 Mataram, dengan subjek terdiri atas dua kelompok belajar yaitu kelas XI IPA-2 dan XI IPA-6 (pembelajaran kooperatif model LT), sedangkan kelas XI IPA-3 dan XI IPA-5 dengan pembelajaran langsung. Pemecahan masalah kimia dengan teknik pathway diberlakukan sebagai variabel kontrol digunakan oleh kedua kelompok siswa. Data h asil penelitian dianalisis dengan One-way Analysis of Variance (ANOVA) pada taraf signifikansi 0,05. Diperoleh kesimpulan bahwa penerapan paduan pembelajaran kooperatif model LT dan pemecahan masalah kimia dengan teknik pathway tidak menunjukkan adanya perbedaan pemahaman konseptual kimia siswa apabila dibandingkan dengan pembelajaran langsung. Paduan strategi pembelajaran kooperatif model LT dan pemecahan masalah kimia dengan teknik pathway menunjukkan hasil yang lebih baik apabila dibandingkan dengan pembelajaran langsung dalam pemahaman algoritmik kimia siswa.